A critique to the mediatization of the 2019 Venezuelan crisis - Valdebenito, Jorge; Berríos, Christian (Re-presentaciones: Periodismo, comunicación y sociedad, 2025)
This article explores the media controversies that occurred during the 2019 Venezuelan presidential-humanitarian crisis. Marked by Juan Guaidó's self-proclamation as interim president, the event attracted media attention. While certain agents highlight the hostility of the opposition and U.S. imperialism, others appealed to the ineffectiveness of the Venezuelan government, aided by Russian and Chinese interests. This study examines the strategies used by the international press to cover controversies about the origin, development and resolution milestones of this crisis in the contemporary era.
Keywords: Venezuela; crisis; comunicación; conflict; international press